2016
DOI: 10.1371/journal.pone.0153550
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD47 Treatment Stimulates Phagocytosis of Glioblastoma by M1 and M2 Polarized Macrophages and Promotes M1 Polarized Macrophages In Vivo

Abstract: Tumor-associated macrophages (TAMs) represent an important cellular subset within the glioblastoma (WHO grade IV) microenvironment and are a potential therapeutic target. TAMs display a continuum of different polarization states between antitumorigenic M1 and protumorigenic M2 phenotypes, with a lower M1/M2 ratio correlating with worse prognosis. Here, we investigated the effect of macrophage polarization on anti-CD47 antibody-mediated phagocytosis of human glioblastoma cells in vitro, as well as the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
206
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 245 publications
(232 citation statements)
references
References 58 publications
10
206
0
Order By: Relevance
“…However, M2 macrophages may exhibit a greater capacity for phagocytosis in response to therapeutic antibody relative to proinflammatory M1 macrophages (41). A recent report has also demonstrated that both M1 and M2 macrophages perform phagocytosis in response to anti-CD47 treatment (42). Furthermore, treatment with anti-CD47 antibodies converted tumor-associated macrophages to an M1-like state in vivo (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, M2 macrophages may exhibit a greater capacity for phagocytosis in response to therapeutic antibody relative to proinflammatory M1 macrophages (41). A recent report has also demonstrated that both M1 and M2 macrophages perform phagocytosis in response to anti-CD47 treatment (42). Furthermore, treatment with anti-CD47 antibodies converted tumor-associated macrophages to an M1-like state in vivo (42).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report has also demonstrated that both M1 and M2 macrophages perform phagocytosis in response to anti-CD47 treatment (42). Furthermore, treatment with anti-CD47 antibodies converted tumor-associated macrophages to an M1-like state in vivo (42). The dichotomy of M1 versus M2 polarization underrepresents the complexity of macrophage activation, which is dynamic and fluid with a plethora of potential activation states (30,43).…”
Section: Discussionmentioning
confidence: 99%
“…M1 macrophages exhibit anti-tumor activity and M2 macrophages exhibit pro-tumor activity (36). It has been demonstrated that blocking CD47-SIRPα signaling with anti-CD47 antibodies enhances phagocytic activity from M1 and M2 macrophages and promotes tumor regression (37). Furthermore, blocking CD47-SIRPα signaling enhances the macrophage phagocytosis of various tumor cells in vitro (18,22,38).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, several research groups focused on M2-like TAMs as a potential targets for anticancer therapies and have gained encouraging results. In addition, skewing TAM differentiation away from the M2 to M1 phenotype promoted antitumor immune responses and reduced tumor growth and metastasis in hepatocellular carcinoma (HCC), prostate cancer, breast cancer and glioblastoma13141516. Furthermore, M1-type macrophages have been reported to be associated with prolonged survival time in patients with non small-cell lung cancer (NSCLC)1718.…”
mentioning
confidence: 99%
“…These compounds include the natural products zoledronic acid19 and emodin20, therapeutic monoclonal antibodies including anti-CD471321 and the phosphatidylserine-targeting antibody 2aG414, and chemotherapy agents, doxycycline and metformin2223. Chlorogenic acid (5-caffeoylquinic acid, CHA), the ester formed between caffeic acid and quinic acid24, is a phenolic compound found in the human diet, in coffee, apples, pears and in green tea.…”
mentioning
confidence: 99%